Relocation in Tseki & Phuthaditjhaba: A comparative ethnography of planned & unplanned removals in Qwaqwa - Niehaus, Isak A. (My University, 1998)
The dominant theme in the recent history of Qwaqwa has been the relocation of thousands of people from "common" South Africa into the "homeland". In 1929 Ross (1930: 88) estimated that the population of Witzieshoek (as Qwaqwa was then known) was 8000 and wrote: In the past few years many folk who could make no existence on the farms outside have moved in. They are the old folk and the poor. This would have to be prohibited because Witzieshoek is already full, or Witzieshoek would have to be enlarged by the addition of nearby farms. (My translation). Subsequent estimates of Qwaqwa's population are: 23 860 in 1970 (BENSO 1978: 9), at least 300 000 in 1980 (Murray 1985: 289) and between 400 000 and 500 000 people in 1982 (Sharp 1982: 13). These figures are suggestive of mass population relocations It is generally possible to distinguish three sending areas. Murray (1985:290) estimates that perhaps 60% of people relocated to Qwaqwa came off white-owned farms, particularly in the northern, eastern and northwestern districts of the Orange Free State (OFS). The remaining 40%, he suggests, came from towns such as Harrismith, Bethlehem, Senekal, Vereeniging, Klerksdorp and Bloemfontein. A relatively small number of people have also been relocated from other "homelands"…. This paper is particularly concerned with highlighting the diverse implications of relocation for different sections of Qwaqwa's population. Despite the conceptual difficulties involved the the concepts "forced" and "voluntary", it is my intention to show that such distinctions may indeed be valuable in understanding relocation processes. It is argued that "official" removals imply at least some prior planning by the state to cater for the needs of those affected. Evidence indicates that people subject to forced removals from OFS townships by the state have enjoyed favourable access to resources and amenities in the 'homeland'. Such people are highly noticeable and taken account of by government and administration in the subsequent allocation of services in the 'homeland'. By contrast, former inhabitants OFS rural areas who have unofficially made their way into the 'homeland's' closer settlements have been severely disadvantaged. Their removals were unplanned and no administrative provisions had been made to meet even their most basic needs. Subsequently they have been largely unnoticed in the allocation of services. This paper reports the results of fieldwork undertaken in the Apollo (plural Diapollo) housing section in the town of Phuthaditjhaba (from August 1984 until February 1985) and the closer settlement of Tseki (in April, June-July and December 1983). The housing section was opened for settlement in March 1971.
African Studies Seminar series. Paper presented August 1989.
Keywords: Forced migration. South Africa. Qwaqwa.; Land settlement. South Africa. Qwaqwa